Advances in virus research. Volume 52 - Maramorosch, Karl.; Murphy, Frederick A.; Shatkin, Aaron J.; ScienceDirect eBooks (New York : Academic Press, 1999)
This series should help in maintaining an overview of various facets of the rapidly expanding fields of virology. Coverage includes: picornaviruses; epidemiology, virology and molecular biology; and a special section on retroviral integration.
Picornaviruses: Epitopes, Canyons, and Pockets; Naturally Occurring Variants of Hepatitis B Virus; Kaposi's Sarcoma-Associated Herpesvirus: Epidemiology, Virology, and Molecular Biology; Role of Chemokine Receptors in HIV-1 Infection and Pathogenesis; Special Section: Retrviral Integration; Nuclear Import of Human Immunodeficiency Virus Type-1 Preintegration Complexes; Host Proteins in Retroviral cDNA Integration; HIV lntegrase Structure and Function; Crystal Structures of Catalytic Core Domains of Retroviral lntegrases and Role of Divalent Cations in Enzymatic Activity; HIV-1 Integrase: Structural Organization, Conformational Changes, and Catalysis; Substrate Recognition by Retroviral lntegrases; Reconstitution of Concerted DNA Integration with Purified Components; In Vivo Analysis of Retroviral Integrase Structure and Function; Inhibitors of Human Immunodeficiency Virus Integrase.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Virology -- Research; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Virology -- Research; Electronic books